ANALISIS PROSPEK PENGEMBANGAN USAHATANI DURIAN (Durio Zibethinus Murray) DI KOTA SEMARANG - Dita Nora Oktaviana; M Handayani; Agus Setiadi (Universitas Wahid Hasyim, 2017)
This research aims to find out the correct development strategies which could be applied on Durian agribusiness in Semarang Region. District of Gunungpati is a well-known durian production center in Semarang Region. The purposes of this research are to find out the development of this business, the profit gained, problem faced by the businessman, and to find out the development strategies. The location was chosen purposively based on the huge crop potential on durian business. The respondents was chosen using purposive sampling. Data analyzed using descriptive-quantitative method, and SWOT analyzed. The results are the identification of business’ development since the productivity increased from 74 kg/tree to 77kg/tree. Durian agribusiness in Semarang region stand on Stability state in SWOT diagram. Keywords : Development prospect, Durian, SWOT